The Impact of EDI on Serials Management: Don't Let the Ship Sail Without You - Simser, Charlene N.; Vukas, Rachel R.; Stephens, Joan M. (The Serials librarian, 2001)
Two representatives from different parts of the electronic data interchange (EDI) process teamed up for a workshop on the impact of EDI on serials management. The presenters were: Charlene N. Simser, Electronic Resource/Serials Librarian and Interim Chair, Technical Services, Kansas State University; and Rachel R. Vukas, Account Services Manager, EBSCO Information Services. The two provided a general background of EDI, and then used the EDI implementation at Kansas State University to illustrate topics to consider when bringing EDI into your library.